Focus and Exceptional Case Marking in Causative Constructions in Standard Arabic - Khadija Farkad; Jamaa Ouchouid (Indonesian Scientific Publication, 2025)
This paper examines the syntactic behavior of causative constructions in Arabic, focusing on the unresolved issue of thematic role and case assignment due to the bi-clausal structure of these constructions. The central research question revolves around the structural position of the causee in Arabic causatives. While prior studies have broadly described causatives in Arabic, they have not sufficiently addressed the syntactic mechanisms underlying the positioning and licensing of the causee within a minimalist framework. This paper offers a novel analysis, grounded in native speaker judgments and syntactic diagnostics, revealing that the causee occupies a contrastive focus position. The findings show that while the thematic role of the causee is assigned by the embedded verb, its case is exceptionally marked by the matrix verb. The causee occupies a contrastive focus position that can host clitic-left dislocated (CLLD) DPs. The dislocated DP resumes a clitic rather than leaving a gap. However, unlike similar positions in matrix clauses, this position does not permit DP stacking. These results indicate that focus positions in Arabic are more structurally diverse than previously thought, with important implications for our understanding of information structure and case assignment in bi-clausal constructions.